Epistemic authority a theory of trust, authority, and autonomy in belief - Zagzebski, Linda Trinkaus, 1946- (Oxford : Oxford University Press, 2013)
In this book Zagzebski gives an extended argument that the self-reflective person is committed to belief on authority. Epistemic authority is compatible with autonomy, but epistemic self-reliance is incoherent. She argues that epistemic and emotional self-trust are rational and inescapable, that consistent self-trust commits us to trust in others, and that among those we are committed to trusting are some whom we ought to treat as epistemic authorities, modeled on the well-known principles of authority of Joseph Raz. These principles apply to authority in the moral and religious domains.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Nov. 13, 2012).
Keywords: Authority; Knowledge, Theory of; Self; Trust